Pharmaceutical Composition of a Dermal Gel Comprising Diclofenacdiethylamine and Lemongrass Oil for Anti-inflammatory and Analgesic Activity - Shri, Tanu; Arockia Babu, M. (International Journal of Psychosocial Rehabilitation, 2019)
The localized reaction that results in redness caused by hyperaemia, tumor and pain caused by infection, irritation or injury may be defined as inflammation. External or internal inflammation can occur. Increasing inflammation is characterized by vasodilation, exuded fluids and infiltrated neutrophi. Analgesics are agents that function selectively in pain reduction without affecting the consciousness, working in the CNS and in the peripheral pain mediators. The analgesics can be narcotics or non-drug products, however. The study of animal suffering causes social, emotional and technical problems. In this study, we used a novel combination of diclofenacdiethylamine and lemongrass oil in the formulation of pharmaceutical dermal gel. Diclofenacdiethylamine is an established non-steroidal anti-inflammative agent commonly used for symptomatic relief of pain and inflammation in musculoskeletal disturbances, arthritis, toothache, dysmenorrhea, etc. Diclofenacdiethylammonium salt is stated for use in topical applications (Diclofenacdiethylamine). Just 10% diclofenac is clinically available from the latest topical formulations. Lemongrass oil is not only the essential skin partition, it interacts and temporarily increases skin permeability with stratum corneum constituents, but also has additional treatment characteristics, such as antiinflammatory, anti-piling and antibacterial properties that help combat nervous exhaustion, tones of the muscles and tissues. Lemongrass oils are also an essential oil. An advanced topical formulation with good penetration increases the permeation of the medicine’s skin tremendously. Therefore, diclofenacdiethylamine and lemongrass oil were developed for a pharmaceutical dermal gel with film-forming capacity.